Answer:
Explanation:
each letter of the alphabet is worth two more than its preceding letter,it means that the worth of each letter is increasing in arithmetic progression. We would apply the formula for determining the nth term of an arithmetic progression. I is expressed as
Tn = a + (n - 1)d
Where
n represents the number of terms in the arithmetic sequence.
d represents the common difference of the terms in the arithmetic sequence.
a represents the first term of the arithmetic sequence.
Tn represents the nth term
From the information given,
n = 26 letters
a = 1
d = 3 - 1 = 2(difference between 2 letters)
Therefore,
T26 = 1 + (26 - 1)2
T26 = 51
The formula for determining the sum of n terms of an arithmetic sequence is expressed as
Sn = n/2[2a + (n - 1)d]
Therefore, the sum of the first 26 terms, S26 would be
S26 = 20/2[2 × 1 + (26 - 1)2]
S26 = 13[2 + 50)
S26 = 13 × 52 = 676